2020
DOI: 10.1164/rccm.201907-1284oc
|View full text |Cite|
|
Sign up to set email alerts
|

Pitolisant for Daytime Sleepiness in Patients with Obstructive Sleep Apnea Who Refuse Continuous Positive Airway Pressure Treatment. A Randomized Trial

Abstract: Rationale: Excessive daytime sleepiness is a common disabling symptom in obstructive sleep apnea syndrome. Objectives: To evaluate the efficacy and safety of pitolisant, a selective histamine H3 receptor antagonist with wake-promoting effects, for the treatment of daytime sleepiness in patients with moderate to severe obstructive sleep apnea refusing continuous positive airway pressure treatment. Methods: In an international, multicenter, double-blind, randomized (3:1), placebo-controlled, parallel-design tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(59 citation statements)
references
References 32 publications
(38 reference statements)
2
52
0
5
Order By: Relevance
“…Procedures were similar to those of the companion study. 16 Randomization was centralized and performed via a website (Arone Projection; https://www.bioprojet-studies.org/). Randomization was on a 3:1 (three pitolisant for one placebo) basis (e-Appendix 1).…”
Section: Randomization and Masking Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures were similar to those of the companion study. 16 Randomization was centralized and performed via a website (Arone Projection; https://www.bioprojet-studies.org/). Randomization was on a 3:1 (three pitolisant for one placebo) basis (e-Appendix 1).…”
Section: Randomization and Masking Proceduresmentioning
confidence: 99%
“…[13][14][15] We recently reported that pitolisant significantly reduced self-reported daytime sleepiness and fatigue and improved patient-reported outcomes and physician disease severity assessment in the specific phenotype of sleepy individuals with OSA who decline CPAP or are nonadherent to CPAP therapy. 16 The evaluation of pitolisant needs to be completed in the different subgroup of OSA individuals: those exhibiting residual sleepiness, despite good adherence to CPAP treatment. The objectives of the present study were to demonstrate the efficacy and safety of pitolisant given at 5 mg, 10 mg, or 20 mg once daily vs placebo over 12 weeks for the treatment of residual EDS in individuals undergoing well-managed CPAP therapy for moderate to severe OSA.…”
mentioning
confidence: 99%
“…H 3 receptor negatively controls histamine synthesis and release as an autoreceptor and also regulates the release of other neurotransmitters such as dopamine, ACh, noradrenaline, adrenaline, glutamate and GABA (Nieto-Alamilla et al, 2016). Although expression levels of HRH3 in peripheral tissues are low (Lovenberg et al, 1999) (Dauvilliers et al, 2020;Liguori et al, 2020), Prader-Willi syndrome (Pullen et al, 2019) and anorexia nervosa (Scolnick, 2019 Fukui et al (1994). b Inoue et al (1996).…”
Section: Histamine H 3 Receptormentioning
confidence: 99%
“…Only one clinical study assessing the efficacy of pitolisant in OSA has been published [38]. In the phase III, double-blind, placebo-controlled, parallel-group, multicenter trial, 268 patients with moderate to severe obstructive sleep apnea, who had refused treatment with CPAP were randomized and given placebo or pitolisant.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%